The Critical Roles of the SUMO-Specific Protease SENP3 in Human Diseases and Clinical Implications - Long, Xiaojun; Zhao, Biying; Lu, Wenbin; Chen, Xu; Yang, Xinyi; Huang, Jifang; Zhang, Yuhong; An, Siming; Qin, Yuanyuan; Xing, Zhengcao; Shen, Yajie; Wu, Hongmei; et al. (Frontiers in Physiology, 2020)
SUMO (small ubiquitin-like modifier) proteins covalently conjugate lysine residues in a large number of target proteins. SUMO modification (SUMOylation) has emerged as an important regulatory mechanism for protein stability, function, subcellular localization, and protein-protein interactions, and thus regulates life activities. SENP3, one of SENP family, de-conjugates the target proteins to adjust the protein modification. The effect of the modification via SUMO and SENP3 is crucial for protein function and life activities. If the SUMOylation process of proteins is affected, it will cause a cellular reaction and ultimately lead to diseases, including cardiovascular diseases, neurological diseases, and various cancers. Targeting SENP3 alone or in combination with current therapies might provide powerful targeted therapeutic strategies for the treatment of these diseases.